Prevalence of Smoking among Workers of the Dr. Gustavo Aldereguía Lima University General Hospital - Teresa Rodríguez Rodríguez; Ahmed Pomares Ávalos (Revista Finlay)
Background: excessive tobacco use is considered the largest epidemic of the twentieth century and the risk factor that contributes the most to the leading causes of morbidity and mortality from chronic non-communicable diseases. Objective: to determine the prevalence of smoking among workers of the Dr. Gustavo Aldereguía Lima University Hospital in Cienfuegos, and its link with chronic non-communicable diseases. Methods: a correlational and cross-sectional study was conducted with workers of the Dr. Gustavo Aldereguía Lima University General Hospital in Cienfuegos between September and December 2009. The study population consisted of 1056 workers. Variables selected were: sex, age, occupation, educational level, chronic diseases, smoking, readiness to quit and professional assistance. The Smoking Survey developed by the Carmen project and modified to meet the objectives of the study was used. Results: prevalence of smoking in the hospital is high (21.9 %). Men smoke more than women (31.8 %). It is more common in those with less than a 12 grade (30.9 %), laborers (30.0 %), followed by dentists (27.1 %) and workers aged 50 to 60 years (33.0 %). People with chronic conditions that smoke the most are the hypertensive (22, 7 %), followed by the asthmatic (12.5 %). Conclusions: prevalence of smoking among hospital workers is high, and low perception of the risk is evident even in those who are suffering from chronic non-communicable diseases.